Patient dose reduction by changing the amount of 18F-FDG radiopharmaceutical injected - Fernanda Guerra Paiva; Priscilla Carmo Santana; Arnaldo Prata Mourão Filho (Brazilian Journal of Radiation Sciences)
Images of Positron Emission Tomography (PET) associated with Computed Tomography (CT) have important diagnostic applications, mainly for oncology. These compound tomographic devices allow the overlapping of functional images obtained from the administration of radiopharmaceuticals and anatomical images generated by X-ray beam attenuation. This work evaluated the impact of reducing the effective dose by reducing the activity injected into the patient using the ICRP 106 biokinetic model. The activity to be injected may vary according to the patient mass and the detector sensitivity. In this work was used the fixed mass of Alderson phantoms, as a standard adult, this mass is 73.5 kg for the male, and 50 kg for the female. Different values of activity to be injected were simulated, from 0.07 mCi to 0.15 mCi per kg, and with 10 mCi fixed, protocol used in some services. Thus, for the acquisition of PET scans, any reduction of the administered activity implies a proportional reduction of the effective dose in patient. The effective dose may vary up to 114% altering the injected activity between 0.07 and 0.15 mCi. The fixed value of 10 mCi is between these variations. It is expected that the PET/CT scans protocols are changed at the end of the study, so that the absorbed and effective dose received by the patient decreases.